GEOMORPHOLOGY OF SMALL ISLANDS AND ITS SEAFLOOR PROFILES IN THE EASTERN AND WESTERN HALMAHERA WATERS - Abdul Motalib Angkotasan; Dietriech G Bengen; I Wayan Nurjaya; Neviaty P Zamani; Nyoman M.N Natih; Franto Novico (Marine Geological Institute of Indonesia, 2022)
The geomorphology of small islands in the eastern and western parts of Halmahera Island encompasses diversities of geological processes, island forms and types, and topography. The typology of the small islands to the west of Halmahera Island is volcanic and are categorized as hilly islands. To the east, there are coral islands classified as flat islands with smaller area contrast to volcanic ones. This study aims to analyze the land mass elevation of the small islands and the sub-bottom profiles in the eastern and western Halmahera waters. Island elevation data was obtained from Sentinel-2B imagery, whereas seafloor topographic data was acquired from direct field measurements using a GPS sounder. First, the image data underwent atmospheric, radiometric, and sunlight corrections, while the actual depth was estimated through bathymetry correction using tidal data. Then, QGIS version 3.16.6 and ArcGIS version 10.8 were used to analyze the data. The results show that the slope degree of volcanic islands is higher and their seafloor topography is steeper than that of coral islands. The slope degree of Ternate, Maitara, Tidore, and Hiri Islands, abbreviated as Termadoreh, is more than 30o with elevation of more than 100 meters, characterizing hilly islands. While there is only Pakal Island in Buli Bay that has a slope of 33o and the highest elevation of only 100 meters, it is nevertheless considered a flat island. Significantly, the different typologies indicate different morphogenesis and sub-bottom topography; i.e., volcanic islands have higher slope degrees and steeper seafloor profiles compared to coral islands.